Socioeconomic Impact of Foot and Mouth Disease Outbreaks on Smallholder Cattle Farmers in Yogyakarta, Indonesia - Agung Triatmojo; Budi Guntoro; Péter Strausz; Mujtahidah Anggriani Ummul Muzayyanah; Robi Agustiar; Szilvia Kusza (Veterinary Sciences, 2025)
Foot and Mouth Disease (FMD) poses significant challenges to livestock management and agricultural economies worldwide. This study examines the effect of farmers’ sociodemographic factors on livestock infected with Foot and Mouth Disease (FMD) and analyzes its socioeconomic impact on smallholder farmers in Indonesia. This study collected data from 992 households (202 infected and 790 non-infected) in the special region of Yogyakarta province. The research used propensity score matching (PSM) treatment effect analysis to assess the socioeconomic impact of FMD outbreaks on smallholder farmers. Our results demonstrated that FMD significantly increased (p < 0.01) smallholder farmers’ social behavior, including knowledge, attitude, and practice (KAP). Furthermore, farmers whose animals are already infected with FMD must spend an additional IDR 258,000 to IDR 270,000 on treatment compared to non-infected ones. This study provides empirical evidence that farmer characteristics, including women’s decision-making, income, farming group, and cattle ownership, determine the likelihood of FMD infection, which implies that farmers with specific characteristics may heighten the risk of FMD infection. We concluded that FMD has changed social behavior and accelerated economic loss for smallholder farmers. Hence, farmers with animals at risk of FMD infection are prioritized in FMD control programs.